The Impact of Verbal Bullying on Learning Motivation in Middle School Students - Alzamaniarta, Alra Octava; Safitri, Anisa; Widyaningrum, Karina; Prihatiningsih, Riskiyana; Istiyawati, Ary; Probowati, Devy (Universitas Negeri Malang, 2024)
Verbal bullying occurs when someone uses verbal power to intimidate others who are perceived as weak. The purpose of this study is to determine the influence of verbal bullying on the learning motivation of eighth-grade students at SMPN 1 Pakis. This research employs correlation methods and simple linear regression data analysis. The sampling technique used is simple random sampling with a total of 90 students. The instruments used in this research are the learning motivation scale and the verbal bullying scale. The research instruments have passed validity and reliability tests. The results of the study show that verbal bullying has an effect on students' learning motivation, as indicated by the hypothesis test which shows 0.000 less than 0.05. The regression coefficient is positive and the hypothesis can be accepted. This study highlights the importance of providing guidance and counseling services that can help reduce verbal bullying, thereby enhancing learning motivation.